Revolutions and revolutionary movements - DeFronzo, James (Westview Press, A Member of the Perseus Books Group, 2019)
"With crucial insights and indispensable information concerning modern-day political upheavals, Revolutions and Revolutionary Movements provides a representative cross section of the most significant revolutions of the twentieth and twenty-first centuries. This Fifth Edition is revised and updated with a new chapter on the Arab Revolution from its beginning in December 2010 to the present. In this widely used text, students can trace the historical development of eleven revolutions using a five-factor analytical framework. Author James DeFronzo clearly explains all relevant concepts and events, the roles of key leaders, and the interrelation of each revolutionary movement with international economic and political developments and conflicts, including World Wars I and II, the Cold War, and the War on Terror. Student resources include multiple orienting maps, summary and analysis sections, suggested readings, chronologies, and documentary resources"-- Provided by publisher.